Anti-cancer peptides: their current trends in the development of peptide-based therapy and anti-tumor drugs. Issue 1 (2nd January 2023) - Lath, Amit; Santal, Anita Rani; Kaur, Nameet; Kumari, Poonam; Singh, Nater Pal
ABSTRACT: Human cancer remains a cause of high mortality throughout the world. The conventional methods and therapies currently employed for treatment are followed by moderate-to-severe side effects. They have not generated curative results due to the ineffectiveness of treatments. Besides, the associated high costs, technical requirements, and cytotoxicity further characterize their limitations. Due to relatively higher presidencies, bioactive peptides with anti-cancer attributes have recently become treatment choices within the therapeutic arsenal. The peptides act as potential anti-cancer agents explicitly targeting tumor cells while being less toxic to normal cells. The anti-cancer peptides are isolated from various natural sources, exhibit high selectivity and high penetration efficiency, and could be quickly restructured. The therapeutic benefits of compatible anti-cancer peptides have contributed to the significant expansion of cancer treatment; albeit, the mechanisms by which bioactive peptides inhibit the proliferation of tumor cells remain unclear. This review will provide a framework for assessing anti-cancer peptides' structural and functional aspects. It shall provide appropriate information on their mode of action to support and strengthen efforts to improve cancer prevention. The article will mention the therapeutic health benefits of anti-cancer peptides. Their importance in clinical studies is elaborated for reducing cancer incidences and developing sustainable treatment models.